Towards a critical pedagogy of place for environmental conservation - Ajaps, Sandra; Forh Mbah, Marcellus (Environmental Education Research, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1080/13504622.2022.2050889 5072953:EKR6HMCP openalex: W4220771464
Keywords: _z:class:countries; _z:class:themes; oa:keyword:critical pedagogy; oa:keyword:environmental conservation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12997 Experiential Education and Adventure Therapy; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:n:1; openalex:yes

Deconstructing Community-Based Research for Sustainable Development: The Role of Indigenous Knowledge Holders - Ajaps, Sandra; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_4 5072953:Y2Y5Q6AF
Keywords: _z:class:countries; _z:class:themes

Indigenous Methodologies, Research and Practices for Sustainable Development - Mbah, Marcellus F.; Leal Filho, Walter; Ajaps, Sandra (Springer Nature, 2022)
KerkoCite.ItemAlsoKnownAs: 5072953:G2X2SHFW
Keywords: _z:class:countries; _z:class:themes

Envisioning the Indigenised university for sustainable development - Mbah, Marcellus Forh; Ajaps, Sandra; Johnson, Ane Turner; Yaffa, Sidat (International Journal of Sustainability in Higher Education, 2022)
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-09-2021-0413 5072953:CCFEHKYQ openalex: W4229372231
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenised university; oa:keyword:sustainable development; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Envisioning the Indigenised university for sustainable development - Mbah, Marcellus Forh; Ajaps, Sandra; Johnson, Ane Turner; Yaffa, Sidat (International Journal of Sustainability in Higher Education, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1108/IJSHE-09-2021-0413 5072953:CCFEHKYQ openalex: W4229372231
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenised university; oa:keyword:sustainable development; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Decolonisation of Research Methodologies for Sustainable Development in Indigenous Settings - Mbah, Marcellus F.; Bailey, Megan (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_2 5072953:VTA2GCYA
Keywords: _z:class:countries; _z:class:themes

Public Health Education in Africa: The Case of Epistemic (in) Justice and Indigenous Health Systems - Orjinta, Amarachi Jane-Frances; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Series Title: World Sustainability Series KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_13 5072953:BMP34WX6
Keywords: _z:class:countries; _z:class:themes

Towards an Integrated Approach to Climate Change Education in Tanzania: The Role of Indigenous Knowledge Systems - Mugabe, Paschal Arsein; Mbah, Marcellus; Apollo, Abigael; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
There have been many efforts globally toward fighting climate change; including international agreements, conferences, research, policies, forums, etc. In addition to these efforts, climate change education has recently emerged as an essential capacity-building tool to curb the climate crisis. However, development practitioners from the Global South have cited limitations with climate change education due to the dominance of Eurocentric epistemologies over indigenous knowledge (IK) approaches. This study therefore advocates for the integration of indigenous knowledge into climate change education in Tanzania for achieving a sustainable environment. Seventy documents, including peer-reviewed papers, reports from corporate institutions, policy briefs, proceedings and other grey literature were reviewed. We establish that IK systems are not integrated into CCE in Tanzania. However, we find opportunities for integration due to the evidence of the existing CCE efforts and potential complementary indigenous practices. By identifying, documenting, and validating indigenous knowledge and merging this knowledge with scientific insights, the fostering of an integrated approach to combat the enduring effects of climate change can be evidenced.
openalex:W4312587358 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_16 5072953:7MNR46WW 5072953:F3ACIBMT
Keywords: C:Tanzania; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:indigenous knowledge systems; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:n:1; openalex:yes